2019
DOI: 10.22460/infinity.v8i2.p209-218
|View full text |Cite
|
Sign up to set email alerts
|

Developing of Calculus Teaching Materials Based on Audiovisual

Abstract: Komunitas  milenium saat ini lebih memilih media video sebagai sumber belajar daripada membaca buku teks. Untuk memahami isi buku, kita perlu memiliki kemampuan baca tulis yang cukup tinggi. Berbeda halnya dengan video pembelajaran,  penjelasan yang disertai dengan gambar dalam video dapat membantu seseorang untuk memahami materi di media itu. Tujuan pertama dari penelitian ini adalah membuat bahan ajar audiovisual yang bisa berfungsi sebagai bahan ajar buku pelajaran tambahan. Tujuan kedua adalah menguji keef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Based on results notes field that learning video playback is very helpful student understand by comprehensive something theory study. Finding this in line with results study (Nasrum & Herlina, 2019) who stated that use of learning videos could increase results study student.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Based on results notes field that learning video playback is very helpful student understand by comprehensive something theory study. Finding this in line with results study (Nasrum & Herlina, 2019) who stated that use of learning videos could increase results study student.…”
Section: Discussionsupporting
confidence: 87%
“…Learning using video has the advantage that it can accommodate audio and visual learning styles. Several studies have also found that the use of video/audio visuals can improve learning outcomes, such as in research (Nasrum & Herlina, 2019)which revealed that with video learning students can repeat less material _ understood anytime and anywhere with replay video even without the presence of a lecturer .…”
Section: Tutorial Videomentioning
confidence: 99%
“…Based on the results of the study on indicators of desire in learning, as many as 78% of students were excited about looking for mathematics learning on the website, in this case the use of interactive multimedia had an important effect in increasing students' enthusiasm for learning. The use of multimedia in the form of audio, text, video, and animation increases student motivation during the learning process (Almara'beh et al, 2015;Leow & Neo, 2014;Maria et al, 2019;Nasrum & Herlina, 2019;Setiawan et al, 2015). Using this website can better support the online learning system in the midst of this pandemic besides using the Learning Management System (LMS) platform, video conferencing, and others (Djamdjuri & Kamilah, 2020;Handayani & Utami, 2020;Lubis & Sari, 2020;Nartiningrum & Nugroho, 2020;Putri & Irwansyah, 2020;Wiratomo & Mulyatna, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the problems encountered were related to students' ability to translate sentences into mathematical models (Boonen et al, 2016). The application of mathematics in life is not applied in the learning process in the class (Nasrum & Herlina, 2019;Setiyani, Putri, & Prakarsa, 2019;Yunianta, Putri, & Kusuma, 2019). Mathematics books focus on solving mathematics analytically and are heavy for students (Nurharyanto & Retnawati, 2020).…”
Section: Introductionmentioning
confidence: 99%